Defective replication initiation results in locus specific chromosome breakage and a ribosomal RNA deficiency in yeast - Sanchez, Joseph C. (PLoS Genet, 2017)
A form of dwarfism known as Meier-Gorlin syndrome (MGS) is caused by recessive mutations in one of six different genes (ORC1, ORC4, ORC6, CDC6, CDT1, and MCM5). These genes encode components of the pre-replication complex, which assembles at origins of replication prior to S phase. Also, variants in two additional replication initiation genes have joined the list of causative mutations for MGS (Geminin and CDC45). The identity of the causative MGS genetic variants strongly suggests that some aspect of replication is amiss in MGS patients; however, little evidence has been obtained regarding what aspect of chromosome replication is faulty. Since the site of one of the missense mutations in the human ORC4 alleles is conserved between humans and yeast, we sought to determine in what way this single amino acid change affects the process of chromosome replication, by introducing the comparable mutation into yeast (orc4(Y232C)). We find that yeast cells with the orc4(Y232C) allele have a prolonged S-phase, due to compromised replication initiation at the ribosomal DNA (rDNA) locus located on chromosome XII. The inability to initiate replication at the rDNA locus results in chromosome breakage and a severely reduced rDNA copy number in the survivors, presumably helping to ensure complete replication of chromosome XII. Although reducing rDNA copy number may help ensure complete chromosome replication, orc4(Y232C) cells struggle to meet the high demand for ribosomal RNA synthesis. This finding provides additional evidence linking two essential cellular pathways—DNA replication and ribosome biogenesis.